The life Abu Hanifa and his methods of fiqh as the object of the pedagogical research - D.U., Atadjonova (The journal of contemporary issues in business and government, 2021)
In the following article the life and methods of fiqh of Abu Hanifa and the researches on the Abu Hanifa, the researches on Abu Hanifa, his teaching is widely revealed. At the same time the opinions of the scholars of Islamic studies on Abu Hanifa are presented.